Analisis Korelasi antara Tingkat Pendidikan Orang Tua dan Kelancaran Hafalan Juz ‘Amma - Askoning Askoning; Rofiatul Hosna (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This article proves the correlation between parental education level and the ability to memorize juz 'amma fluency in Al-Mustaghfiroh Jombang Kindergarten students. This research was conducted on students in early childhood education, namely at Kindergarten B Al-Mustaghfiroh Jombang. The method in this research was carried out through a quantitative approach using documentation studies. The data previously obtained was processed using descriptive analysis, percentage formulas, standard deviations and Contingency Coefficient Correlation analysis. In this case, the research results show that this research is very suitable for identifying students' learning processes, including relationships that influence the learning process or students' memory during their golden age. Second, the educational level of the parents of Al-Mustaghfiroh Kindergarten students, which is in the high category, is 25% or as many as 5 people who are Bachelor graduates; the medium category is 70%, or as many as 14 people who are high school graduates and finally the low category is only 1 person or as much as 5% are elementary school graduates. Al-Mustaghfiroh Kindergarten students' ability to memorize fluency was included in the high category with a score of > 70.00 for as many as 7 people, 11 people in the medium category got a score of 60.00 - 69.00 and only 2 people in the low category with a score of < 59.00. From this, it can be seen that there is a positive and significant correlation between the level of parental education and the fluent memorization ability of Al-Mustaghfiroh Kindergarten students at a significance level of 5% or ?=0.05 with ?_0 > ?_tabel / 0.74998 > 0.444 so reject H_0 and H_a accepted. and vice versa, namely 25.002% influenced by other factors.